Fluoride as a preventive agent for dental caries: A narrative review (Research, Society and Development, 2025)
Dental caries is a chronic, multifactorial disease characterized by the progressive demineralization of teeth. Despite advances in dentistry, the prevalence of caries remains high, especially among children. Fluoride has emerged as an essential preventive agent due to its ability to promote dental remineralization and inhibit the cariogenic process. This study aims to review the literature on the use of fluoridated agents in dental caries prevention, with a focus on their application in Pediatric Dentistry. The methodology involved a narrative literature review, with article searches in the PubMed and Scopus databases using the Health Science Descriptors "fluoride," "pediatric dentistry," and "fluoridated agents." Original and review studies published in English, Portuguese, and Spanish that addressed the use of fluoride in caries prevention in children were selected. The article analysis allowed for the compilation of data on the mechanisms of action, efficacy, and safety of fluoride, as well as its indications for different age groups. The study concludes by highlighting the importance of fluoride in dental caries prevention, emphasizing the rational and safe use of fluoride based on scientific evidence as an essential practice for children's oral health.